A self-supported amorphous Ni–P alloy on a CuO nanowire array: an efficient 3D electrode catalyst for water splitting in alkaline media. Issue 19 (19th February 2018) - Chang, Bing; Hao, Shuai; Ye, Zhixiang; Yang, Yingchun
Abstract : An amorphous Ni–P alloy shell electrodeposited on a CuO nanowire array to synergistically boost the catalytic activity toward alkaline water splitting is reported, and this core@shell CuO@Ni–P nanowire array is durable with a cell voltage of only 1.71 V reaching a current density of 30 mA cm −2 using a two-electrode configuration in an alkaline water electrolyzer. Abstract : Energy-efficient electrochemical water splitting is one important way to produce hydrogen fuel but still faces many challenges. In this communication, we report that an amorphous Ni–P alloy shell electrodeposited on a CuO nanowire array supported on copper foam (CuO@Ni–P NA/CF) can be used for efficient water splitting in alkaline media. As a 3D catalytic electrode, it exhibits excellent activity both for the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER) with overpotentials of 106 mV for HER and 275 mV for OER to achieve a current density of 30 mA cm −2 in 1.0 M KOH. This bifunctional electrode enables a high-performance alkaline water electrolyzer to achieve a current density of 30 mA cm −2 at a cell voltage of 1.71 V.